Mahātma Gāndhī : caritra, kāmagirī, āṇi śikavaṇa - Dāmale, Sītārāma Keśava, 1878-1927 (SAMP early 20th-century Indian books project, 1924)
On the life and works of Mahatma Gandhi, 1869-1948, Indian nationalist.